Cognitive Processing in New and Practiced Discrete Keying Sequences - Verwey, Willem B.; Abrahamse, Elger L.; De Kleine, Elian (Frontiers in Psychology, 2010)
This study addresses the role of cognitive control in the initiation and execution of familiar and unfamiliar movement sequences. To become familiar with two movement sequences participants first practiced two discrete key press sequences by responding to two fixed series of 6 key specific stimuli. In the ensuing test phase they executed these two familiar and also two unfamiliar keying sequences while there was a two-third chance a tone was presented together with one randomly selected key specific stimulus in each sequence. In the counting condition of the test phase participants counted the low pitched (i.e., target) tones. By and large the results support the dual processor model in which the prime role of the cognitive processor shifts from executing to initiating sequences while the gradual development of motor chunks allows a motor processor to execute the sequences. Yet, the results extend this simple model by suggesting that with little practice sequence execution is based also on some non-cognitive (perhaps associative) learning mechanism and, for some participants, on the use of explicit sequence knowledge. Also, after extensive practice the cognitive processor appears to still contribute to slower responses. The occurrence of long interkey intervals was replicated suggesting that fixed 6-key sequences include several motor chunks. Yet, no indication was found that the cognitive processor is responsible for concatenating these chunks.